2016
DOI: 10.1038/nphys3760
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the superconducting phase of sulfur hydride

Abstract: A superconducting critical temperature above 200 K has recently been discovered in H2S (or D2S) under high hydrostatic pressure1, 2. These measurements were interpreted in terms of a decomposition of these materials into elemental sulfur and a hydrogen-rich hydride that is responsible for the superconductivity, although direct experimental evidence for this mechanism has so far been lacking. Here we report the crystal structure of the superconducting phase of hydrogen sulfide (and deuterium sulfide) in the nor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

54
414
2
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 454 publications
(483 citation statements)
references
References 27 publications
54
414
2
5
Order By: Relevance
“…Although possibilities of unconventional mechanisms are still under investigation [6,21,[23][24][25], these first-principles results strongly suggest that the phonon-mediated pairing has a pivotal role, which is also in accord with the experimentally observed hydrogen isotope effect [1]. According to the recent X-ray diffraction measurement [2], the observed record Tc is not of the solid phases of H 2 S, but of its decomposition product H 3 S. In prior to the first experimental discovery, P1 and Cmca phases of H 2 S and R3m and Im3m phases of H 3 S have been predicted to be stable and metallic at pressures above 100 GPa [3,4]. In particular, the electron-phonon coupling in the latter phases has been estimated to be strong enough to reproduce the experimentally observed Tc over 200 K [3,4].…”
Section: Introductionsupporting
confidence: 68%
See 2 more Smart Citations
“…Although possibilities of unconventional mechanisms are still under investigation [6,21,[23][24][25], these first-principles results strongly suggest that the phonon-mediated pairing has a pivotal role, which is also in accord with the experimentally observed hydrogen isotope effect [1]. According to the recent X-ray diffraction measurement [2], the observed record Tc is not of the solid phases of H 2 S, but of its decomposition product H 3 S. In prior to the first experimental discovery, P1 and Cmca phases of H 2 S and R3m and Im3m phases of H 3 S have been predicted to be stable and metallic at pressures above 100 GPa [3,4]. In particular, the electron-phonon coupling in the latter phases has been estimated to be strong enough to reproduce the experimentally observed Tc over 200 K [3,4].…”
Section: Introductionsupporting
confidence: 68%
“…The recent discovery of high-temperature superconductivity in compressed H 2 S [1,2] has tremendous impact on the basic science. Its maximum transition temperature (Tc) is as high as 203K, which is higher than the long-standing champion data observed in Hg-cuprate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical studies, which have shown that the superconductivity observed in Ref. [38] arises primarily from an H 3 S phase [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] whose structure has been recently confirmed experimentally [56], will not be described within this short review. We will, however, discuss the results of first principles calculations carried out for the hydrides of phosphorus [57][58][59].…”
Section: Introductionmentioning
confidence: 99%
“…Searches over a much smaller number of stoichiometries were performed by Duan et al 29 Errea et al 17 also showed that anharmonic vibrations significantly reduce the T c of H 3 S-Im3m. The high-pressure cubic structure of H 3 S of space group Im3m in which the sulfur atoms lie on a body-centered cubic (bcc) lattice has now been confirmed by X-ray diffraction experiments, 30 see Fig. 1.…”
Section: Introductionmentioning
confidence: 81%